2015
DOI: 10.1007/s10461-015-1189-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Factors and Condom Use Among Women with a History of Intimate Partner Violence

Abstract: Women who experience intimate partner violence (IPV) are at increased risk for HIV infection. To further the understanding of the dyadic factors that impact condom use among women, we investigated the impact of three relationship factors (i.e., power, fear, and dependence) on the association between HIV-related information, motivation, and behavioral skills [constructs from the Information-Motivation-Behavioral Skills (IMB) model] and condom use among abused women. Data from 133 urban, low-income women recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(36 reference statements)
0
13
0
1
Order By: Relevance
“…A number of studies suggest that IPV is associated with reduced selfefficacy for negotiating condom use. Some studies suggest that an imbalance in relationship power, defined as "the extent to which one person can influence and control their partner's behavior and dominate decision-making within the dyad" (McGrane Minton et al, 2016) may be the pathway through which IPV affects condom use, either instead of or in addition to reduced condom self-efficacy (Bonacquisti and Geller, 2013). An alternative hypothesis is that IPV is a marker for male controlling behaviors and that a woman's male partner may try to regulate her fertility (Hung et al, 2012;Miller et al, 2011;Moore et al, 2010), a construct called reproductive coercion or reproductive control (Silverman and Raj, 2014).…”
Section: Mechanism Through Which Intimate Partner Violence Affects Comentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies suggest that IPV is associated with reduced selfefficacy for negotiating condom use. Some studies suggest that an imbalance in relationship power, defined as "the extent to which one person can influence and control their partner's behavior and dominate decision-making within the dyad" (McGrane Minton et al, 2016) may be the pathway through which IPV affects condom use, either instead of or in addition to reduced condom self-efficacy (Bonacquisti and Geller, 2013). An alternative hypothesis is that IPV is a marker for male controlling behaviors and that a woman's male partner may try to regulate her fertility (Hung et al, 2012;Miller et al, 2011;Moore et al, 2010), a construct called reproductive coercion or reproductive control (Silverman and Raj, 2014).…”
Section: Mechanism Through Which Intimate Partner Violence Affects Comentioning
confidence: 99%
“…An alternative hypothesis is that IPV is a marker for male controlling behaviors and that a woman's male partner may try to regulate her fertility (Hung et al, 2012;Miller et al, 2011;Moore et al, 2010), a construct called reproductive coercion or reproductive control (Silverman and Raj, 2014). Another hypothesis is that women may be less able to use condoms because they fear violent consequences (Bonacquisti and Geller, 2013;McGrane Minton et al, 2016). Within a relationship with a subtext of violence, pregnant women may prioritize the safety of their unborn fetus over the risk of violence associated with negotiating condom use (Hatcher et al, 2014).…”
Section: Mechanism Through Which Intimate Partner Violence Affects Comentioning
confidence: 99%
See 1 more Smart Citation
“…These findings resonate with previous work that postulates having limited power within a relationship and having a fear of abuse from a partner hinders a woman's ability to practise safer sex, which can increase her risk of STI acquisition (McGrane Minton et al . ). Furthermore, these findings support earlier work which concluded that adolescent girls exposed to physical and sexual dating violence are more likely to be diagnosed with an STI than adolescents who are not exposed to such abuse (Decker et al .…”
Section: Discussionmentioning
confidence: 97%
“…These findings are also consistent with those reported by studies that suggest that a woman’s proposal to use a condom might be perceived by her male partner as a sign of distrust or infidelity (Kelly and Kalichman 1995). Other studies have found an association between unprotected vaginal and/or anal sex and intimate partner violence, where fear of abuse can limit a woman’s ability to negotiate condom use (Marin, Gomez, and Tschann 1993; McGrane-Minton et al 2016; Mittal, Stockman, and Seplaki 2013). Having a history of sexual and/or physical abuse also increases a woman’s vulnerability to HIV and other sexually transmitted infections (Wingood and DiClemente 1998).…”
Section: Discussionmentioning
confidence: 99%